Anhedonia in chronic pain and prescription opioid misuse. Issue 12 (19th September 2020) - Garland, Eric L.; Trøstheim, Martin; Eikemo, Marie; Ernst, Gernot; Leknes, Siri
Abstract: Background: Both acute and chronic pain can disrupt reward processing. Moreover, prolonged prescription opioid use and depressed mood are common in chronic pain samples. Despite the prevalence of these risk factors for anhedonia, little is known about anhedonia in chronic pain populations. Methods: We conducted a large-scale, systematic study of anhedonia in chronic pain, focusing on its relationship with opioid use/misuse, pain severity, and depression. Chronic pain patients across four distinct samples ( N = 488) completed the Snaith–Hamilton Pleasure Scale (SHAPS), measures of opioid use, pain severity and depression, as well as the Current Opioid Misuse Measure (COMM). We used a meta-analytic approach to determine reference levels of anhedonia in healthy samples spanning a variety of countries and diverse age groups, extracting SHAPS scores from 58 published studies totaling 2664 psychiatrically healthy participants. Results: Compared to healthy samples, chronic pain patients showed higher levels of anhedonia, with 25% of patients scoring above the standard anhedonia cut-off. This difference was not primarily driven by depression levels, which explained less than 25% of variance in anhedonia scores. Neither opioid use duration, dose, nor pain severity alone was significantly associated with anhedonia. Yet, there was a clear effect of opioid misuse, with opioid misusers (COMM ⩾13) reporting greater anhedonia than non-misusers. Opioid misuse remained a significant predictor of anhedonia even after controlling for pain severity, depression and opioid dose. Conclusions: Study results suggest that both chronic pain and opioid misuse contribute to anhedonia, which may, in turn, drive further pain and misuse.